Dynamics control of nonholonomic system modelling motion of skier and snowboarder - Borisov, A.; Kaspirovich, I.; Mukharlyamov, R. (ANS Conference Series: Scientific Heritage of Sergey A. Chaplygin (Nonholonomic Mechanics, Vortex Structures and Hydrodynamics): Book of Abstracts, 2019)
In this paper a problem of dynamics control of nonholonomic Chaplygin systems is considered. A model of a skier or a snowboarder is chosen as an example of these systems. A structure of its Lagrange function and nonholonomic constraint equations allows us to set up the motion equations in the Chaplygin's form. The control is realized by extra forces defined by the constraints that determine a required motion.